ANALISIS KEMAMPUAN LITERASI NUMERASI SISWA KELAS V SEKOLAH DASAR NEGERI 02 BAKALAN - Mucklis Aji Pranata; Dwi Anggraeni Siwi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the numeracy literacy skills of fifth-grade students at SD Negeri 02 Bakalan and identify the obstacles affecting those skills. Numeracy literacy is an essential ability in understanding and applying mathematical concepts in daily life. This research was motivated by students’ difficulties in understanding contextual problems and relating mathematical concepts to real-life situations. This study employed a qualitative approach with a descriptive method. The research subjects consisted of 12 fifth-grade students at SD Negeri 02 Bakalan. Data were collected through observation, interviews, tests, and documentation. The data were analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results showed that the students’ numeracy literacy skills were in the fairly good category. However, students still experienced difficulties in solving word problems, understanding contextual situations, and interpreting data presented in tables and diagrams. The obstacles affecting students’ numeracy literacy skills included internal factors such as low learning motivation and limited understanding of mathematical concepts, as well as external factors such as limited learning resources and less contextual teaching methods. Therefore, more innovative and contextual learning strategies are needed to improve elementary school students’ numeracy literacy skills.